2003
DOI: 10.1002/cncr.11717
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and quality of life among female long‐term colorectal cancer survivors

Abstract: Nearly pure boron carbide free from impurities was produced on a tungsten substrate in a dual impinging‐jet chemical vapor deposition reactor from a BCl3, CH4, and H2 mixture. The Fourier Transform Infrared (FTIR) analysis proved the formation of reaction intermediate BHCl2, which is proposed to occur mainly in the gaseous boundary layer next to the substrate surface. Among a large number of reaction mechanisms proposed only the ones considering the molecular adsorption of boron carbide on the substrate surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 70 publications
(18 reference statements)
5
95
2
3
Order By: Relevance
“…Sociodemographic and medical factors predictive of poorer psychological outcomes include younger age at diagnosis, being female, having dependent children in the home, economic adversity, lower levels of education, later-stage disease, and high physical burden treatment approaches. [10][11][12][13][14] Psychological variables include predisposing factors such as dispositional optimism; adaptive approaches such as positive threat appraisals; and coping resources such as social support. 11,[15][16][17] Dispositional optimism is proposed as a stable personality characteristic whereby a person has generalized outcome expectancies that lead them to expect either positive or negative outcomes to result from events.…”
Section: Resultsmentioning
confidence: 99%
“…Sociodemographic and medical factors predictive of poorer psychological outcomes include younger age at diagnosis, being female, having dependent children in the home, economic adversity, lower levels of education, later-stage disease, and high physical burden treatment approaches. [10][11][12][13][14] Psychological variables include predisposing factors such as dispositional optimism; adaptive approaches such as positive threat appraisals; and coping resources such as social support. 11,[15][16][17] Dispositional optimism is proposed as a stable personality characteristic whereby a person has generalized outcome expectancies that lead them to expect either positive or negative outcomes to result from events.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have used a range of different instruments in addition to these (29) , as revealed in this review, where 12 (80%) (24) Assessed QoL and its relation with psychosocial aspects, such as anxiety and depression and aspects related to social support offered, including the social network and instrumental, emotional and informational support. Descriptive and exploratory studies -level 6 (19)(20)(21)(22) Controlled randomized clinical trial -level 2 (23) Qualitative, phenomenological -level 6 (24) Role, emotional, social, physical and mental functions. (27) Lis et al 2006 (28) Studies tested the correlation among genders (25) , age ranges (26) , described the difference between well-and malnourished patients (27) and investigated whether QoL predicts survival (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Berkman-Syme Social Network Index (SNI) (20)(21) Centre for Epidemiological Studies Depression scale (CES-D) (16) EORTC Quality of Life Questionnaire Core-30 (QLQ-C30) (19,22,23,(25)(26)(27) EORTC Quality of Life Questionnaire Colorectal-38 (QLQ-CR38) (19,23,(25)(26) Functional Assessment of Cancer Therapy -Colorectal (FACT-C) (14)(15)(16) Functional Assessment of Cancer Therapy -General (FACT-G) (16) Hospital Anxiety and Depression Scale (HADS) (18,(22)(23) Medical Outcomes Study Short-Form 12 (SF-12) (18,21) Medical Outcomes Study Short-Form 36 (SF-36) (20) Nottingham Health Profile (NHP) (17) State-Trait Anxiety Inventory (STAI) (16) Satisfaction With Life Scale (SWLS) (14)(15)(16) The Ferrans and Powers Quality of life Index (QLI) (28) Obs. Notes refer to the articles that used each instrument.…”
Section: Instrumentsmentioning
confidence: 99%
“…Some examples of behavioral changes are having a healthful diet, leaving dangerous behavior such as smoking, alcohol consumption, inactivity, following regular and scheduled visits (Pinquart and Duberstein, 2010;Kim et al, 2015). All mentioned items can lead to enhance quality of life in cancer patients (Sapp et al, 2003;Kroenke et al, 2013).…”
Section: Online Social Network Advantages In Cancer Patient Carementioning
confidence: 99%